The Effect of Employee Attachment and Voice Behavior on Employee Performance through Employee Job Satisfaction as an Intervening Variable at the Branch Office of PT. Bank Sumut in Binjai City - Said Sulaiman; Yeni Absah; Beby Sembiring (Journal of Indonesian Management, 2026)
This study aims to analyze the effect of employee engagement and voice behavior on employee performance with job satisfaction as an intervening variable at the Branch Office of PT. Bank Sumut in Binjai City. This research employs a quantitative approach with a causal associative research design. The population of this study consists of all employees of PT. Bank Sumut Branch Office in Binjai City, totaling 38 employees. The study employed saturated sampling (census method), incorporating all population members as research samples. Data collection involved questionnaires, with analysis conducted via descriptive statistics and the Structural Equation Modeling–Partial Least Square (SEM-PLS) approach. The findings reveal that employee engagement and voice behavior positively and significantly influence job satisfaction. Moreover, job satisfaction positively and significantly impacts employee performance. Additionally, employee engagement and voice behavior positively and significantly affect employee performance, both directly and indirectly via job satisfaction as a mediating variable. These findings suggest that improving employee performance at PT. Bank Sumut Branch Office in Binjai City can be achieved by strengthening employee engagement, encouraging voice behavior, and continuously enhancing job satisfaction.